Diagnostic Test of Randhawa Preoperative Scoring System in Predicting Laparoscopic Cholecystectomy Difficulty - Andreas Andreas; Muhammad Yusuf; Ferry Erdani; Imam Hidayat; Muntadhar Muhammad Isa (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Despite its minimally invasive nature, laparoscopic cholecystectomy carries inherent risks of complications and unplanned conversions to open procedures. Scoring systems, such as the one developed by Randhawa and Pujahari, are used to assess this risk preoperatively. While the Randhawa scoring system shows great performance in the original study, external validation is essential before it can be widely implemented. To address this, we conducted a study with a cross-sectional analytical design where all data prospectively collected to externally validate the diagnostic value of the Rhandawa scoring system in predicting laparoscopic cholecystectomy difficulty. Using consecutive sampling, this study was conducted at the Dr. Zainoel Abidin General Hospital surgical ward and operating theatre between August and December 2025. Patients were evaluated preoperatively one day prior to surgery using the Randhawa scoring system, and intraoperative data, including duration, complications, and conversion, were recorded. Surgical difficulty was classified as easy, difficult, or very difficult based on these findings. Bivariate and multivariate analyses were performed to identify risk factors in the scoring system that were significantly associated with laparoscopic cholecystectomy difficulty. The area under the ROC curve (AUC) was calculated to assess the diagnostic performance of the scoring system, along with sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV). A history of hospitalization for acute cholecystitis was found to be significantly associated with laparoscopic cholecystectomy difficulty in both bivariate (p = 0.009) and multivariate (OR 4.85; 95% CI: 1.52–15.40; p = 0.007) analyses. The preoperative score and laparoscopic cholecystectomy difficulties were found to be significantly associated (p < 0.05). Our findings also demonstrated that the Randhawa preoperative scoring system demonstrated good diagnostic accuracy with an AUC of 0.836. Using a cutoff threshold of ≤5 and >5, the scoring system yielded 56.25% (95% CI: 29.88%–80.25%) sensitivity, 87.5% (95% CI: 67.64%–97.34%) specificity, 75% (95% CI: 57.80%–87.88%) accuracy, 75% (95% CI: 48.11%–90.73%) PPV, and 70% (95% CI: 63.80%–83.66%) NPV. We concluded that the Randhawa preoperative scoring system is reliable and beneficial in predicting laparoscopic cholecystectomy difficulty. Furthermore, we suggest for subsequent multicenter validation with larger patient samples